Defining the parameters for a brush with polypropylene bristle when uncovering the root system of maternal plants - Voitik, Andrii; Kravchenko, Vasyl; Oliadnichuk, Ruslan; Pushka, Olexandr; Kiurchev, Serhii; Ivanov, Oleg; Kharak, Ruslan; Nazarenko, Oleksii (Eastern-European Journal of Enterprise Technologies, 2019)
The paper addresses the operation of a cylindrical brush with elastic rods of bristles at the disclosure of the root system of maternal plants. It has been established that the basic components of the resistance force in the operation of a given brush is the sum of resistances caused by the soil viscosity force, the static resistance of loose particles of soil and the resistance force at removing soil particles. Based on the minimization of costs of energy, the optimal kinematical parameters have been defined for the brush with a vertical rotation axis. The value for the total resistance force is largely affected by the angular speed of the brush. In addition to the resistance force, the rods of the brush bristles are exposed to the normal reaction from the soil base. By deriving the resultant of these two forces using a method of the Legendre elliptic integrals, we have established the optimal dimensional parameters for the rods of bristles made of polypropylene. A given method has made it possible to take into consideration their significant, compared with the rods’ length, deformations as a result of their bending. The rods’ length has been determined to be the maximally possible one to ensure the conditions for the removal of soil from a swath that covers the root system of maternal plants of clonal rootstock. In addition, the influence of the friction force during brush operation has been investigated. This implies friction among soil particles and against the surface of the bristle rods. It was determined that the forces of friction, as well as the normal reaction of soil, have little effect on the operation of a cylindrical brush while opening the root system of maternal plants. This is due to the lack of a solid foundation when a bristle rod is at work, which in turn makes it possible to arrange the bristle rods one by one at the surface of the brush. The absence of necessity in the considerable relative stiffness makes it possible for the bristle rods to remove soil from the swath while minimizing damage to the plants. By using the Legendre elliptic integrals of second kind, we have explored the deflection of bristle rods in a cylindrical brush while opening the root system of maternal plants. The magnitude of the rod deflection during operation affects the degree of it removing the soil particles. An increase in deflection changes the angle between a working facet of the bristle rod and the soil surface. This leads to a decrease in the removal of particles and to an increase in their compaction in a swath. Therefore, we have calculated the length of bristle rods that could ensure the required operating parameters under a predefined load.